Television-optical method for stress-concentration measuring in plastically deformed solids; The 6th International Conference on Multiscaling in Applied Science and Emerging Technologies (University of Patras, Greece, May 31 - June 4, 2004) - Derevyagina L. S.; Panin V. E. Viktor Evgenyevich; Deryugin Ye.Ye.; Strelkova I. L. (2004, 2004)
Strain (stress) distributions in the vicinity of one or more U-notches in tensile flat Cu, NiTi and composite Al+10%Al2O3 specimens are studied. In measuring of field plastic strains the pioneer television-optical rapid method is used. The patterns of strain-rate intensity distribution are plotted and compared with an analytical solution for an elastic region and with results obtained by other methods. Fracture of Al+10%Al2O3 notched specimen develops according to scheme of phase wave